2013
DOI: 10.1111/trf.12409
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of both RHD and RHCE allele frequencies in sub‐Saharan Africa

Abstract: Our data show that frequencies of aberrant RHD and RHCE alleles were similar, irrespective of location and ethnicity. In view of the predicted frequencies and relative clinical significance of both private antigens and high-prevalence antigens absent, the most relevant assays for individuals of African descent in a transfusion setting are for 1) partial RH2 in the patient and 2) RH54 (DAK) in the donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
(34 reference statements)
3
39
0
Order By: Relevance
“…Results of RH genotyping were roughly similar to those of previous data . The most common RHD alleles were belonging to the usual three African D clusters, that is, DAU, DIVa, and weak D Type 4 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results of RH genotyping were roughly similar to those of previous data . The most common RHD alleles were belonging to the usual three African D clusters, that is, DAU, DIVa, and weak D Type 4 .…”
Section: Discussionsupporting
confidence: 86%
“…Genomic DNA was isolated from 200 µL of whole blood using a blood DNA mini‐kit (QIAmp, Qiagen, Courtaboeuf, France) according to the manufacturer's instructions. Polymerase chain reaction (PCR) assay was performed on the 10 exons of the RHD and RHCE genes as previously described . Briefly, amplification was performed with 100 ng of genomic DNA in a final volume of 50 µL containing PCR buffer, 2 mmol/L MgCl 2 , 80 ng/µL bovine serum albumin, 0.2 mmol/L of each dNTP, 0.05 unit of Taq DNA polymerase, and 200 nmol/L of each primer.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported allele prevalences for other populations [18,19,44,45,46]. Partial RH2 antigens appear to be particularly prevalent in mainland France, whereas partial RH1 antigens are more prevalent in Guadeloupe and French Guiana.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were performed by using RHD and RHCE kits (BeadChip, BioArray Solutions, Immucor, Paris, France). Analysis of RHCE from the proposita was performed by polymerase chain reaction (PCR) amplification and sequencing as previously described . Sequence alignment was performed by using computer software (SeqMan Pro, DNA Star, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%